Leptospira interrogans Outer Membrane Protein-Based Nanohybrid Sensor for the Diagnosis of Leptospirosis - Verma, Vivek; Kala, Deepak; Gupta, Shagun; Kumar, Harsh; Kaushal, Ankur; Kuča, Kamil; Cruz-Martins, Natália; Kumar, Dinesh (Sensors (Basel, Switzerland), 2021)
Leptospirosis is an underestimated tropical disease caused by the pathogenic Leptospira species and responsible for several serious health problems. Here, we aimed to develop an ultrasensitive DNA biosensor for the rapid and on-site detection of the Loa22 gene of Leptospira interrogans using a gold nanoparticle-carbon nanofiber composite (AuN/CNF)-based screen-printed electrode. Cyclic voltammetry and electrochemical impedance were performed for electrochemical analysis. The sensitivity of the sensor was 5431.74 μA/cm2/ng with a LOD (detection limit) of 0.0077 ng/μL using cyclic voltammetry. The developed DNA biosensor was found highly specific to the Loa22 gene of L. interrogans, with a storage stability at 4 °C for 180 days and a 6% loss of the initial response. This DNA-based sensor only takes 30 min for rapid detection of the pathogen, with a higher specificity and sensitivity. The promising results obtained suggest the application of the developed sensor as a point of care device for the diagnosis of leptospirosis.
Keywords: leptospiróza; zlato; Loa22 gene; Membrane Proteins; Leptospira interrogans; kovové nanočástice; Gold; lidé; AuN/CNF; Metal Nanoparticles; Leptospirosis; membránové proteiny; DNA sensor; Humans